Prolonged postoperative Ileus: what should be done to improve patient outcome? - Shussman, Noam (Annals of Laparoscopic and Endoscopic Surgery; Vol 3 (March 2018): Annals of Laparoscopic and Endoscopic Surgery, 2018)
Postoperative ileus (POI) is a transient inhibition of gastrointestinal (GI) motility that involves the entire GI tract (1). Prolonged POI is characterized by abdominal distention, nausea, vomiting and delayed passage of flatus and stool. It is defined by two or more of the following criteria occurring on or after the fourth postoperative day without prior resolution of POI: nausea or vomiting, inability to tolerate oral diet over 24 hours, absence of flatus over 24 hours, abdominal distension defined as increased abdominal girth with tympany on percussion, or radiologic confirmation of POI (2).